2010
DOI: 10.1074/jbc.m109.095430
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic Analysis of Schwanniomyces occidentalis Invertase Reveals a New Oligomerization Pattern and the Role of Its Supplementary Domain in Substrate Binding

Abstract: Schwanniomyces occidentalis invertase is an extracellular enzyme that hydrolizes sucrose and releases ␤-fructose from various oligosaccharides and essential storage fructan polymers such as inulin. We report here the three-dimensional structure of Sw. occidentalis invertase at 2.9 Å resolution and its complex with fructose at 1.9 Å resolution. The monomer presents a bimodular arrangement common to other GH32 enzymes, with an N-terminal 5-fold ␤-propeller catalytic domain and a C-terminal ␤-sandwich domain for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 40 publications
(41 reference statements)
8
97
0
Order By: Relevance
“…This construct was used as a template to obtain all the mutants generated in this work. Site-directed mutagenesis was carried out using specific primers, including substitutions responsible for mutations N58S, D80A, N107S, E303A, E334S/E334N/E334V/E334Q, Q341N, N342S, H343A/H343T, N471S, and Y659STOP, and following the method described previously (21). DNA sequencing was used to verify that only the desired mutations were present in all the obtained constructs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This construct was used as a template to obtain all the mutants generated in this work. Site-directed mutagenesis was carried out using specific primers, including substitutions responsible for mutations N58S, D80A, N107S, E303A, E334S/E334N/E334V/E334Q, Q341N, N342S, H343A/H343T, N471S, and Y659STOP, and following the method described previously (21). DNA sequencing was used to verify that only the desired mutations were present in all the obtained constructs.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, GH32 enzymes from bacteria (13,14), fungi (15)(16)(17), and plants (18 -20) have been the subject of many structural studies that showed that all are monomeric enzymes. Surprisingly, studies on Schwanniomyces occidentalis fructofuranosidase (SoFfase) (21) and Saccharomyces cerevisiae invertase (ScINV) (22) showed that these enzymes from yeast are unique in that they form dimers mediated by their ␤-sandwich domain, which in the case of ScINV associate into higher oligomers. The structural studies have delineated the main structural determinants of activity, the loops and turns connecting the different elements of the ␤-propeller domain, in the surroundings of the active site, defining the specificity unique to each enzyme (21,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher 1-kestose levels for the parent highlighted the difference in activities, as this is the initial FOS species produced from sucrose. It in turn serves as the substrate for the formation of nystose and GF 4 . The fructose data for both enzymes were similar, which indicated that the hydrolytic activity was unchanged in the variant.…”
Section: Resultsmentioning
confidence: 99%
“…Also known as invertases (EC 3.2.1.26), they hydrolyze sucrose to produce invert sugar, an equimolar mixture of dextrorotatory D-glucose and levorotatory D-fructose (2). Crystal structures reveal that these enzymes display the bimodular arrangement of an N-terminal catalytic domain containing a fivebladed ␤-propeller fold linked to a C-terminal ␤-sandwich domain (3)(4)(5)(6). Multiple sequence alignments (MSAs) identified a highly conserved aspartate close to the N terminus that serves as the catalytic nucleophile and a glutamate residue that acts as a general acid/base catalyst (7).…”
mentioning
confidence: 99%